2016
DOI: 10.1027/1614-0001/a000182
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness Is the Most Powerful Noncognitive Predictor of School Achievement in Adolescents

Abstract: Abstract. Much research has demonstrated that intelligence and conscientiousness have a high impact on individual school achievement. To figure out if other noncognitive traits have incremental validity over intelligence and conscientiousness, we conducted a study on 498 eighth-grade students from general secondary schools in Austria. Hierarchical regressions for three criteria (GPA, science, and languages) were performed, including intelligence, the Big Five, self-discipline, grit, self-efficacy, intrinsic-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 40 publications
8
94
1
11
Order By: Relevance
“…Among 54 studies that examined the effect of overall grit on students' academic achievement, more than half ( 2009;Duckworth et al, 2007;Dumfart & Neubauer, 2016;Farroll, 2016;Hill, 2016;Huang & Zhu, 2017;B. C. Lee, 2017;Lee & Sohn, 2017;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks et al, 2017;Sheehan, 2014;Strayhorn, 2014;Tovar-García, 2017;Wang et al, 2017;Williams, 2017), whereas one study reported a significant negative result (Climer, 2017).…”
Section: Overall Gritmentioning
confidence: 99%
“…Among 54 studies that examined the effect of overall grit on students' academic achievement, more than half ( 2009;Duckworth et al, 2007;Dumfart & Neubauer, 2016;Farroll, 2016;Hill, 2016;Huang & Zhu, 2017;B. C. Lee, 2017;Lee & Sohn, 2017;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks et al, 2017;Sheehan, 2014;Strayhorn, 2014;Tovar-García, 2017;Wang et al, 2017;Williams, 2017), whereas one study reported a significant negative result (Climer, 2017).…”
Section: Overall Gritmentioning
confidence: 99%
“…We are aware of only two studies that used broader measures of conscientiousness (Dumfart & Neubauer, 2016;MacCann & Roberts, 2010). Only MacCann and Roberts (2010) took a closer look at the relationships between the facets of conscientiousness and grit scores.…”
Section: The Relation Between Grit and Conscientiousnessmentioning
confidence: 99%
“…Although previous research indicated grit a predictor of achievement in areas of academia, military, and the workplace, it is important to note indicator of overall success (Bazelais, Lemay, & Doleck, 2016;Dumfart & Neubauer, 2016;Ivcevic & Brackett, 2014). Dumfart and Neubauer (2016) conducted a study of 498 eighth graders to determine if noncognitive traits had incremental validity over cognitive skill and conscientiousness.…”
Section: Grit and Academicsmentioning
confidence: 99%
“…Dumfart and Neubauer (2016) conducted a study of 498 eighth graders to determine if noncognitive traits had incremental validity over cognitive skill and conscientiousness. Results indicated adolescents high in grit performed slightly better in academics, but conscientiousness was the more important factor, of which grit is one component.…”
Section: Grit and Academicsmentioning
confidence: 99%